Démarginaliser l’intersection de la race et du sexe : une critique féministe noire du droit antidiscriminatoire, de la théorie féministe et des politiques de l’antiracisme - Crenshaw, Kimberlé W. (Droit et société, 2021)
Dans cet article fondateur, K. Crenshaw introduit le concept d’« intersectionnalité », pour penser le caractère composé des effets de subordination liés à des facteurs comme la race, le genre, l’âge, la sexualité, etc. Elle analyse d’abord trois affaires juridiques qui ont traité des questions de discrimination raciale et sexuelle pour montrer les limites des « analyses à enjeu unique » : DeGraffenreid v. General Motors, Moore v. Hughes Helicopter, Inc. et Payne v. Travenol. Dans aucune de ces affaires, les tribunaux n’ont permis aux plaignantes d’alléguer une discrimination fondée à la fois sur la race et le sexe. K. Crenshaw montre qu’il faut penser l’intersectionnalité des discriminations pour saisir et corriger la situation particulière des femmes noires. Dans un second temps, elle élargit la réflexion vers le cadre sociopolitique et suggère que la condition des femmes noires doit être mieux prise en compte tant par les mouvements féministes que par les mouvements anti-racistes.
Première publication: 1989 https://www.cairn.info/revue-droit-et-societe-2021-2-page-465.htm
Keywords: amériques; antiracisme; approches et analyses; cours; discipline; droit; fem1000; incontournable; intersectionnalité; lit4700; militance; premier cycle; racisme; régions géographiques; science politique et droit; systèmes d'oppressions; thématiques; états-unis

Les disparitions de filles et de femmes autochtones à Tiohtiá:ke/Montréal : pour une collaboration réelle entre le SPVM et les milieux autochtones - Femmes autochtones du Québec; Bernier, Dominique; Farget, Doris; Trilsch, Mirja (2020)
Le présent rapport de recherche s’inscrit dans les mobilisations autour de l’enjeu public que représentent les disparitions et les assassinats de femmes ou de filles autochtones au Canada. Considérant que l’autochtonie urbaine est un phénomène important au Québec, que la majorité des cas de disparition et d’assassinat de filles et de femmes autochtones ont lieu en milieu urbain et qu’il existe un manque patent de données portant spécifiquement sur Tiohtiá:ke/Montréal, le présent rapport examine cette « crise sociale » au sein de cet espace urbain. L’objectif de la recherche est de comprendre la réponse du Service de police de la ville de Montréal (SPVM) face à ces disparitions et assassinats. Bien que nos données démontrent qu’il y a consensus autour de la nécessité d’une collaboration entre le SPVM et les organisations communautaires et autochtones pour aborder de manière efficace la problématique, nous avons également constaté de nombreuses difficultés entourant la relation et la collaboration entre le SPVM et les personnes concernées par les disparitions et les assassinats de femmes et de filles autochtones. Des entretiens réalisés auprès de membres du SPVM et d’intervenants et intervenantes et une analyse du discours des personnes participantes, nous permettent de mettre en lumière les différentes dimensions des difficultés dans cette relation de collaboration. Nous soutenons que non seulement le phénomène des femmes et filles autochtones disparues et assassinées doit être saisi en tenant compte du cadre juridique des droits humains, mais la réponse à cette situation de la part des autorités doit également s’y conformer. C’est aussi dans ce cadre que sont formulées les huit recommandations finales adressées au SPVM et aux autorités publiques.
Keywords: amériques; approches et analyses; canada; cours; discipline; disparition; droit; droits des femmes*; droits des femmes* autochtones; histoire et politique; intersectionnalité; montréal; pol4105; police; premier cycle; québec; racisme; régions géographiques; science politique et droit; sciences juridiques; sexisme; système colonial; systèmes d'oppressions; thématiques; tiohtiá:ke; violences

Conférence: «Droit et féminisme - Rencontre entre deux champs» - Institut de recherches et d'études féministes; Réseau Québécois en études féministes (2018)
Avec Rachel Chagnon, membre de l'Institut de recherches et d'études féministes et professeure au Département des sciences juridiques.
Keywords: amériques; approches et analyses; discipline; discours dominant; droit; droits des femmes*; europe; féminisme décolonial; histoire du féminisme; intersectionnalité; inégalités; militance; mouvements des femmes*; rapports sociaux de sexe; ressource en ligne; régions géographiques; science politique et droit; sciences humaines; sciences juridiques; sociologie; système colonial; systèmes d'oppressions; thématiques

Radical reproductive justice: Foundation, theory, practice - Ross, Loretta; Roberts, Lynn; Derkas, Erika; Peoples, Whitney; Bridgewater Toure, Pamela (Feminist press, 2017)
Expanding the social justice discourse surrounding "reproductive rights" to include issues of environmental justice, incarceration, poverty, disability, and more, this crucial anthology explores the practical applications for activist thought migrating from the community into the academy. Radical Reproductive Justice assembles two decades’ of work initiated by SisterSong Women of Color Health Collective, creators of the human rights-based “reproductive justice” framework to move beyond polarized pro-choice/pro-life debates. Rooted in Black feminism and built on intersecting identities, this revolutionary framework asserts a woman's right to have children, to not have children, and to parent and provide for the children they have.
Keywords: afro-féminisme; approches et analyses; discipline; droit; droits des femmes*; intersectionnalité; justice reproductive; justice sociale; maternité; militance; santé; science politique et droit; sciences humaines; sociologie; thématiques

Kimberlé Crenshaw: The urgency of intersectionality | TED Talk - Crenshaw, Kimberlé (TedTalk, 2016)
Now more than ever, it's important to look boldly at the reality of race and gender bias – and understand how the two can combine to create even more harm. Kimberlé Crenshaw uses the term "intersectionality" to describe this phenomenon; as she says, if you're standing in the path of multiple forms of exclusion, you're likely to get hit by both. In this moving talk, she calls on us to bear witness to this reality and speak up for victims of prejudice.
Keywords: activisme; afro-féminisme; approches et analyses; com5170; cours; discipline; droit; droits civiques; droits des femmes*; droits humains; féminisme afroaméricain; histoire et politique; intersectionnalité; justice sociale; militance; premier cycle; science politique et droit; thématiques

Sexualized Violence and Colonialism: Reflections on the Inquiry into Missing and Murdered Indigenous Women - Razack, Sherene (Canadian Journal of Women and the Law, 2016)
Introduction to the special isuue of the Canadian Journal of Women and the Law on the "Missing and Murdered Indigenous Women Conference".
Keywords: 2000 à aujourd'hui; 2010-2019; amériques; approches et analyses; canada; cours; discipline; droit; droits des femmes*; féminicide; intersectionnalité; justice sociale; pol4105; premier cycle; périodes historiques; racisme; régions géographiques; science politique et droit; sexisme; système colonial; systèmes d'oppressions; thématiques; violences

Prison sexual abuse: Race, gender, and the rule of law - Buchanan, Kim (Columbia University, 2010)
In this dissertation, I argue that the exemption of prisons from the rule of law fosters abusive institutional practices that reveal the race and gender dynamics of sexual abuse in prison and in the outside world. The first article, Beyond Modesty: Privacy in Prison and the Risk of Sexual Abuse, shows that Fourth Amendment privacy offers little protection against the cross-gender searches and surveillance that expose women prisoners to sexual abuse by male guards. It proposes a reinterpretation of Fourth Amendment privacy that would recognize a constitutional right to be free from the fear, risk and reality of prison sexual abuse. The second article, Impunity: Sexual Abuse in Women's Prisons, shows that an edifice of constitutional, statutory and common-law rules confers near-complete institutional immunity against nearly all prisoner claims of custodial sexual abuse. These immunity rules parallel those of historical status regimes which excluded low-status litigants from courts on the basis of race and gender, such as civil death, slavery, segregation and the common law of marriage and rape–with similar results: low-status women of color are exposed to systematic and institutionalized sexual abuse, and are prevented from seeking protection or redress from the courts. The third article, Our Prisons, Ourselves: Race, Gender and the Rule of Law, develops these insights in men's prisons. In the absence of enforceable external rules, staff and administrators often adopt a gendered practice of institutional governance that requires prisoners to prove their manhood by fighting, and penalizes unmanly men by allowing others to rape them. These unlawful gendered practices are obscured by a false but powerful racialized narrative: most people inside and outside prison believe, inaccurately, that prison rape is mainly black-on-white. By casting sexual violence as a "complex and intractable" race relations problem for which administrators are not to blame, the racial narrative bolsters the rationale for exempting prison administration from the rule of law. Thus the perception (and reality) of unchecked prison violence supplies a reason for courts not to interfere with the unlawful institutional policies that foster it.
https://clio.columbia.edu/catalog/8481765
Keywords: approches et analyses; criminologie; discipline; droit; genre; intersectionnalité; mémoires/thèses; racisme; ressource en ligne; science politique et droit; sciences humaines; sexisme; systèmes d'oppressions; thématiques; violences; violences sexuelles

Decoding Black Women: Policing Practices and Rape Prosecution on the Streets of Philadelphia - Irving, Toni (NWSA Journal, 2008)
Black women are generally displaced as victims of rape. The police response to the sexual assault of black women in general and lower-class black women in particular is illustrative of how sexual ideologies help construct complex social hierarchies that in turn structure rights. How the law currently deals with rape places black women outside of the narrative frames that legitimate entitlement. Rape continues to stand in for, and effectively obscure, other social, political, and economic concerns. Unpublished and often ignored, the rape narrative is a ripe site to supply oppositional interpretations of national experience and transmit some of the structural problems in the criminal justice system. Pulling from over two thousand “real” rape cases of low-income black women ignored and not investigated in Philadelphia between 1995 and 2000, this article reads black female rape narratives as case studies in order to discuss the way personal narratives of rape victims are structured by competing and overwhelming sociolegal narratives that undercut their reception. As the fastest growing prison population, the presence of the law to punish black women stands in stark contrast to the absence of the law to protect them.
Keywords: 1900-1999; 1990-1999; afro-féminisme; amériques; approches et analyses; arts; corps; cours; discipline; droit; droit des femmes* noires; droits des femmes*; féminisme afroaméricain; histoire et politique; intersectionnalité; inégalités; philadelphie; premier cycle; périodes historiques; racisme; ressource en ligne; régions géographiques; science politique; science politique et droit; sex2283; sexisme; systèmes d'oppressions; thématiques; viol; violences; états-unis; études littéraires